Comparison Analysis Of Bubble Sort And Insertion Sort Algorithm On The Selection Of A Shop According To The Criteria - Deandy Zahran Vierdansyah; Ghalbin Al Ghafiqi; Muhammad Taufik Dwi Putra; Deden Pradeka (Journal of Computer Engineering, Electronics and Information Technology, 2023)
In choosing a place to open a business was very important and must be considered. One of the suitable places to open a business was a kiosk. This study aimed to facilitate the public in determining the location of the sales kiosk. This was motivated by the limitations and speed in accessing information about the location of the kiosk. In this study, there was a process system for comparing execution time analysis using the Bubble Sort and Insertion Sort algorithms based on the criteria that had been provided. There were criteria that could be selected by users, including the location of the sales kiosk, the area and the available kiosk rental price per year. So that this research system could overcome community problems in terms of limitations and the speed of accessing information that was less efficient about the location of the sales kiosk. After the implementation and analysis of execution time on sales kiosk data as many as 10 places in the C++ programming language using Codeblocks, the results obtained were the use of the Insertion Short algorithm, the use of the Insertion Sort algorithm was more effective in sorting the kiosk places according to the criteria provided.